Accountability of a Notary in Court for Underhand Deed Legalized by a Notary - Agung Aditya (Faculty of Law, Universitas Pekalongan, 2021)
This research aims to provide an explanation of the responsibility of notary public in the Court of deed under the hands of a notary public, facts in the field show that a Notary is often called to the court to give testimony on the evidence of the trial, namely a letter under the hand legalized by the notary, therefore there needs to be an explanation of the notary's liability for the deed made or legalized. Notary responsibility for deed under legalized hands is heavier than waarmerking, because the parties sign before notary public where notary does not ascertain the content of a deed whether it is wrong or true. Although only legalization but the deed under the hand has the value of being a valid and strong evidence in court so that sometimes dragging a notary witness in the trial. Notary can be subject to criminal sanctions if they are proven to have harmed one of the parties and the Notary can also be subject to civil sanctions in the form of compensation according to what was suffered by the parties.